Modelo de gestión económica del colegio particular a distancia “república de argentina” extensión La Maná - Ugsha Chusin, María Yolanda (2016)
In this research project about economic management of Private School "Republic of Argentina" from La Maná Cotopaxi Province, based on the technical study - scientific research work, which is based on the application of a documentary verification, student surveys, and interview to the coordinator of the school. When conducting the analysis of results it was concluded that does not have a model own economic management of the institution and not financial instruments handled due to excessive accumulation of functions in a single department, giving rise to a pressure meet innumerable tasks within the institution. For which it is necessary to perform all procedures attached to the current regulations to have a clear understanding of the objectives, which allow financially support this institution, to make technical decisions, that the authorities do not make investments by pure intuition, with the consequent risk of loss. Based on the research of this issue, conclusions and recommendations will be established, whose main point is the application of a model of economic management, covering a reorganization of this department, establishing the necessary functions and their relationships in order to get the best result in economic management. The proposal also includes functions, procedures, records and control systems for the entire economic process. This process of financial analysis was performed in order to support managers of the institution in the evaluation, allowing provide information for making appropriate decisions.